2020
DOI: 10.1007/978-3-030-50921-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Challenges of Symmetry in Participatory Science Education Research – Proposing a Heuristic for Ethical Reflection

Abstract: The advancement of participatory methodologies and educational action research has raised challenges of research ethics that concern the relations between different actors. Different forms of participatory research rest on cooperation between teachers, researchers, and students in different forms of relations. The ways in which these relations are enacted are often related to research objectives, epistemology, the people involved in the study, and the context in which the study is carried out. In this chapter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Still, we recognize that predetermined guidelines can never fully encompass all the complex issues that may emerge in a teacher-researcher collaboration. For the sake of shared ownership, we concur with other researchers that there is need to invite teachers to be agents in research and to adopt a contextualized approach to research ethics, aligned with the 'everyday ethics' of teacher practice that include instant professional judgements as well as school rules and management expectations (Andrée, Danckwardt-Lillieström, and Wiblom 2020;Bryan and Burstow 2018;Mockler 2014). However, as Jones and Stanley (2010) point out, we realize that such a change would require that higher-education institutions re-examine the nature of their relationships with public stakeholders as well as the political context in which such relations are embedded.…”
Section: Rights and Obligations Associated With Ownershipsupporting
confidence: 67%
See 1 more Smart Citation
“…Still, we recognize that predetermined guidelines can never fully encompass all the complex issues that may emerge in a teacher-researcher collaboration. For the sake of shared ownership, we concur with other researchers that there is need to invite teachers to be agents in research and to adopt a contextualized approach to research ethics, aligned with the 'everyday ethics' of teacher practice that include instant professional judgements as well as school rules and management expectations (Andrée, Danckwardt-Lillieström, and Wiblom 2020;Bryan and Burstow 2018;Mockler 2014). However, as Jones and Stanley (2010) point out, we realize that such a change would require that higher-education institutions re-examine the nature of their relationships with public stakeholders as well as the political context in which such relations are embedded.…”
Section: Rights and Obligations Associated With Ownershipsupporting
confidence: 67%
“…Sensevy et al (2013) have suggested that teacher-researcher collaborations should rest on a principle of symmetry, implying the participants' equal responsibilities throughout the entire research process. However, in practice, a principle of symmetry is farfetched since teacher-researcher relationships typically are loaded with inequalities in terms of who has the higher status, who holds the funding, who states the problem, who has local practical knowledge, who interprets the joint work, and who writes its story (Andrée, Danckwardt-Lillieström, and Wiblom 2020;Bae 2005;Gutiérrez and Penuel 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this context researchers and teachers have tried to work in a symmetrical and complementary atmosphere, where the action also has resulted in the co-writing of this article. The entire cooperation has further amounted to a constant reflection regarding ontological, epistemological and methodological ideas (Andrée et al, 2020). The ontological perspective includes reflection based on how the students' learning is influenced by the action and the admittance of the values at stake.…”
Section: Ethical Standpointsmentioning
confidence: 99%
“…These were mostly about the negotiations about a shared research object where the goals of the action became gathering of new information regarding the didactical potential for VR in education. Finally, the reflections regarding the methodological perspective were mostly about how the empirical data can be interpreted based on different teaching theories, a discussion that turned out to be educational for all parties (Andrée et al, 2020).…”
Section: Ethical Standpointsmentioning
confidence: 99%